B-cell-specific depletion of tumour necrosis factor alpha inhibits atherosclerosis development and plaque vulnerability to rupture by reducing cell death and inflammation. Issue 4 (4th August 2016) - Tay, Christopher; Liu, Yu-Han; Hosseini, Hamid; Kanellakis, Peter; Cao, Anh; Peter, Karlheinz; Tipping, Peter; Bobik, Alex; Toh, Ban-Hock; Kyaw, Tin
Abstract: Aims  B2 lymphocytes promote atherosclerosis development but their mechanisms of action are unknown. Here, we investigated the role of tumour necrosis factor alpha (TNF-α) produced by B2 cells in atherogenesis. Methods and results  We found that 50% of TNF-α-producing spleen lymphocytes were B2 cells and ∼20% of spleen and aortic B cells produced TNF-α in hyperlipidemic ApoE −/− mice. We generated mixed bone marrow (80% μMT/20% TNF-α −/− ) chimeric LDLR −/− mice where only B cells did not express TNF-α. Atherosclerosis was reduced in chimeric LDLR −/− mice with TNF-α-deficient B cells. TNF-α expression in atherosclerotic lesions and in macrophages were also reduced accompanied by fewer apoptotic cells, reduced necrotic cores, and reduced lesion Fas, interleukin-1β and MCP-1 in mice with TNF-α-deficient B cells compared to mice with TNF-α-sufficient B cells. To confirm that the reduced atherosclerosis is attributable to B2 cells, we transferred wild-type and TNF-α-deficient B2 cells into ApoE −/− mice deficient in B cells or in lymphocytes. After 8 weeks of high fat diet, we found that atherosclerosis was increased by wild-type but not TNF-α-deficient B2 cells. Lesions of mice with wild-type B2 cells but not TNF-α-deficient B2 cells also had increased apoptotic cells and necrotic cores. Transferred B2 cells were found in lesions of recipient mice, suggesting that TNF-α-producing B2 cells promote atherosclerosis within lesions. Conclusion  We conclude that TNF-α produced by B2 cells is a key mechanism by which B2 cells promote atherogenesis through augmenting macrophage TNF-α production to induce cell death and inflammation that promote plaque vulnerability.